Implementation and verification of a masonry panel model for nonlinear dynamic analysis of infilled RC frames - Smyrou, E.; Blandon, C.; Antoniou, S.; Pinho, R.; Crisafulli, F. (Bulletin of earthquake engineering, 2011)
The effect of infill panels on the response of RC frames subjected to seismic action is widely recognised and has been subject of numerous experimental investigations, while several attempts to model it analytically have been reported. In this work, the implementation, within a fibre-based Finite Elements program, of a double-strut nonlinear cyclic model for unreinforced masonry panels is carried out. The adequacy of the model in predicting the cyclic/seismic response of multi-storey infilled reinforced concrete frames is then verified through comparisons against experimental results.